Jenis dan Dosis Latihan Intradialisis yang Meningkatkan Kualitas Hidup Pasien Hemodialisa - Hilda Anggraeni Laluyan; Indasah Indasah; Agusta Dian Ellina; Katmini Katmini (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
There are many risk factors for chronic kidney disease (CKD), one of which is age over 65 years and female sex. Hemodialysis is a way of treating stage 5 CKD, given in the long term so that it has an impact on various aspects of life. Patients can experience mental, social and physical disorders. Intradialysis exercises are exercises performed during a hemodialysis session. The purpose of doing this exercise is to increase muscle strength, shorten hospitalization time, improve blood pressure control, improve fat quality, and increase the effectiveness of dialysis. This study is a literature review involving 15 journal articles. The review results show that progressive resistance training is the most appropriate choice. This exercise can improve the patient's physical and psychological health, improve quality of life, reduce the risk of swelling and pain, and improve respiratory function. The dose of exercise three times per week is quite safe for patients. Exercise for 12 weeks can significantly improve the quality of life of hemodialysis patients.Keywords: hemodialysis; intradialysis exercises; quality of life ABSTRAK Banyak faktor resiko chronic kidney disease (CKD), salah satunya adalah usia di atas 65 tahun serta  jenis kemain perempuan. Hemodialisis merupakan salah satu cara pengobatan CKD tahap 5, diberikan dalam jangka panjang sehingga berdampak bagi berbagai aspek kehidupan. Pasien dapat mengalami gangguan mental, sosial maupun fisik. Latihan intradialisis adalah latihan yang dilakukan selama sesi hemodialisa. Tujuan dilakukannya latihan ini adalah untuk meningkatkan kekuatan otot, mempersingkat waktu rawat inap, meningkatkan kontrol tekanan darah, meningkatkan kualitas lemak, dan meningkatkan efektifitas dialisis. Studi ini merupakan literature review yang melibatkan 15 artikel jurnal. Hasil review menunjukkan bahwa progressive resistance training menjadi pilihan yang paling tepat. Latihan ini dapat meningkatkan kesehatan fisik dan psikologis pasien, meningkatkan kualitas hidup, menurunkan resiko bengkak dan nyeri, serta meningkatkan fungsi pernapasan. Dosis latihan tiga kali perminggu cukup aman bagi pasien. Latihan selama 12 minggu dapat meningkatkan kualitas hidup pasien hemodialisis secara signifikan.Kata kunci: hemodialisa; latihan intradialisis; kualitas hidup